The recirculated aquaculture system (RAS) development with nanobubble application to improve growth performance of grouper fish fry culture - Hanif, Iik Muslihul; Effendi, Irzal; Budiardi, Tatag; Diatin, Iis (Indonesian Society of Scientific Aquaculture (ISSA), 2021)
One of the aquaculture commodities with high economic value is grouper fish (Epinephelus sp.). RAS is known as one of superior and suitable aquaculture systems in juvenile fish culture. RAS installed with NBs is expected to increase the stocking density and production of hybrid brown-marbled grouper. This study aimed to analyze the system performance of grouper fish juvenile culture in high stocking density with water exchange system, RAS, and combination of RAS and NBs. This study used a factorial design with two factors, namely different stocking densities and cultivation systems. The densities were 500, 600 and 700 fish/m3, while the treatment systems were RAS without NBs, RAS installed with NBs, and control treatment with 200% water change. Each treatment was replicated three times. The total aquaria used for this study were 27 as each size was 1.5 m × 0.5 m × 0.5 m. The study results showed that the RAS installed with NBs and a stocking density of 600 fish/m2 showed the best results on fish production performance. Keywords: density, growth, grouper, nanobubble, RAS ABSTRAK Pendederan ikan kerapu meripakan salah satu segmen dalam usaha budidaya ikan kerapu (Epinephelus sp.). Salah satu sistem akuakultur yang cocok yang dapat digunakan dalam pendederan ikan kerapu ini adalah sistem recirculated aquaculture system (RAS). RAS dengan instalasi nanobubble (NBs) ini diharapkan bisa meningkatkan padat tebar dan kinerja produksi benih ikan kerapu. Penelitian ini bertujuan untuk menganalisis kinerja sistem pendederan ikan kerapu dengan padat tebar tinggi berbasis sistem pergantian air, RAS, dan perpaduan antara RAS dan NBs. Rancangan percobaan yang digunakan dalam penelitian ini adalah faktorial dengan dua faktor, yaitu padat tebar dan sistem budidaya berbeda. Padat tebar yang digunakan adalah 500, 600, dan 700 ekor/m3, sedangkan sistem budidaya terdiri dari RAS tanpa NBs, RAS dengan NBs dan kontrol (sistem pergantian air 200%), setiap perlakuan terdiri dari atas tiga ulangan. Hasil penelitian menunjukkan bahwa pendederan menggunakan RAS dengan NBs dengan padat tebar 600 ekor/m2 menunjukkan kinerja produksi ikan kerapu yang terbaik. Kata kunci: ikan kerapu, kepadatan, nanobubble, pertumbuhan, RAS